Distinct Neural Processes for Memorizing Form and Meaning Within Sentences - Mascelloni, Matteo; Zamparelli, Roberto; Vespignani, Francesco; Gruber, Thomas; Mueller, Jutta L. (Frontiers in Human Neuroscience, 2019)
Working memory for sentences may comprise both processes of language comprehension during encoding and processes of language production during maintenance including articulatory but also higher-level planning processes. While the former processes are easily testable via controlled presentation of the input, the latter are more difficult to assess directly as language production is typically initiated and controlled internally. In the present ERP study, we track subvocal rehearsal of sentences with the help of a silent cued-production task. Native German participants read different types of sentences word-by-word, then a visual cue triggered the silent production of each individual word in a rehearsal phase. The sentences were either correct, contained a semantic or a syntactic violation, or had random word order. Significant ERP effects were found during reading as well as during silent production. Semantic violations during reading elicited an N400 effect at the noun following the verb and syntactic violations led to a local P600 effect at the noun following the determiner. Different ERP patterns occurred during the silent production phase. Here, semantically violated sentences elicited an early fronto-central negativity at the verb, while syntactically violated sentences elicited a late right-frontal positivity at the determiner. Random word order was accompanied by long-lasting slow waves during the production phase. The findings are consistent with models of hierarchical sentence planning and further indicate that the ongoing working memory processes are qualitatively distinct from comprehension mechanisms and neurophysiologically specific for syntactic and lexical-semantic level planning. In conclusion, active working memory maintenance of sentences is likely to comprise specific stages of sentence production that are indicated by ERP correlates of advanced syntactic and semantic planning at the phrasal and clausal level respectively.